Reading-writing academic discursive genres as a formative process of a teaching degree class to PARFOR - Rodrigues, Jéssica do Nascimento; Mello, Marcela Tavares de (The ESPecialist, 2023)
This qualitative-interpretative research focuses on the evaluative evaluations of students, already teachers, of a Pedagogy course linked to PARFOR, about the difficulties of inclusion in the daily practices of university writing and the work developed by the university professor in the teaching of academic genres in the course of courses. Methodologically, a semistructured questionnaire answered orally in videotape by three students in 2018. Understanding that writing practices are social practices located in discursive spheres not exempt from hierarchical, ideological and power relations, this debate is anchored in Literacy Studies, Enunciation Theory and research that imbricate teacher training and academic literacy. Valuation assessments produced indicate that there are “hidden dimensions” between the solicitation and the production of academic genres, whose writing is stimulated/ demanded systematically by professor. Although value judgments indicate the acquisition of more experience with this modality, the assumption that students should not only know how to master these genres in advance is a factor that impedes meaningful writing experiences, because it minimizes the space of teaching in academic sphere.